Health-related quality of life of hemophilics and its possible correlates: A perspective in health promotion and disability prevention - Soumyaneel Das; Rabindra Nath Roy; Dilip Kumar Das; Amitava Chakraborty; Raston Mondal (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Clinical evaluations are not sufficient to adequately characterize the morbidity associated with hemophilia. Quality of life (QoL) of hemophilics and associated factors is not well explored in Indian research. The present study aimed to measure the QoL in hemophilics and its association with socio-demographic characteristics and other characteristics. MATERIALS AND METHODS: A cross-sectional study was conducted during June-November 2018. Two hundred and one hemophilics (age ≥ 4 years) were interviewed with a pre-tested schedule for sociodemographic and other relevant variables. QoL was measured by Haemo-QoL questionnaire for different pediatric age groups and Haem-A-QoL questionnaire for adults and assigned health-related QoL scores. Score achieved in each dimension as well as total scores were transformed on scales ranging from 0 to 100, high values indicate high impairment of QoL. Hemophilic arthropathy was assessed using the World Federation of Hemophilia Joint Scores. One-way ANOVA, independent t-test, Kruskal-Wallis test, and Spearman correlation analyses were performed using SPSS version 16. RESULTS: Mean Haemo-QoL scores for 4-7 years, 8-12 years, 13-16 years, and >16 years were 43.92 ± 8.09, 37.37 ± 8.62, 32.79 ± 6.66, and 45.92 ± 6.30, respectively. Significant difference was noted for QoL scores across different age groups, grades of severity, educational, occupational categories, socioeconomic status classes, marital status, and presence or absence of target joint. Total QoL scores, as well as scores in some of the dimensions, showed a significant positive correlation with the World Federation of Hemophilia joint scores by Spearman correlation analysis. CONCLUSIONS: Improvement of the joint health status by regular physiotherapy is needed to improve the QoL of hemophilics.